Controle de fitopatógenos com extratos vegetais - Barros, Liliane Silva de (2015)
Worldwide, along with population growths comes the demand for more healthy foods. Among the factors that reduce food production, fungal diseases are of great relevance. These diseases are traditionally controlled using agrochemical. However, the increasing demand for products free of chemical residuals has incentivized research into alternative treatments. Studies have shown that plantbased extracts show potential as an alternative control against diseases. The objective of this work is to select and evaluate the effect of plant-based extracts on phytopathogenic fungi and seed germination. Chapter 1, “Vegetable Extracts of Cerrado plants induce Phytoalexin Production”, evaluates extracts of fresh and dry leaves on phytoalexin production in mesocotyls of Sorghum bicolor L. Results show that aqueous extracts of cashew, cerejeira, jequitibá, pequi, lixeira, baru, timbó, aroeira, tarumã and cambará all activated the production of phytoalexins “in vitro”, demonstrating that these plants have the ability to assist in the activation of plant defense mechanisms. Aqueous extracts of dry leaves of timbó and aroeira were the most efficient phytoalexin inducers for sorghum mesocotyls. In Chapter 2, “Inhibition of mycelial growth and sclerotia production of Sclerotinia sclerotiorum with plant extracts”, the objective was to evaluate inhibition of mycelial growth and sclerotia production of Sclerotinia sclerotiorum, using aqueous extracts of fresh and dry leaves of cerrado plants. Sterile aqueous extracts of fresh leaves inhibited mycelial growth of S. Sclerotiorum. We found that sterilized extracts of dry leaves resulted in a lower number and weight of sclerotia, whereas extracts based on fresh leaves only reduced the number of sclerotia. The use of sterilized aqueous plant extracts based on fresh cashew, pequi and aroeira leaves, and non-sterilized aqueous extracts of pequi and jequitibá stimulate mycelial development of S. sclerotiorum. In Chapter III, “Plant extracts for the alternative treatment of Guizotia abyssinica seeds”, I aim to evaluate the potential of plant extracts, in powder and ethanol-based solutions, for treatment of Niger seeds. It was found that ethanol-based extracts of nim, mutamba and a powdered extract of mutamba controlled 100% of Cladosporium sp. and Aspergillus sp. An ethanol-based extract of mango reduced the germination of niger seeds by 18%. In Chapter IV, “Plant extracts for the alternative treatment of Triticum aestivum seeds” the effect of different plant extracts on the treatment and germination of five varieties of wheat seeds was evaluated. It was found that treatment using an aqueous extract of black pepper is effective for the controlo of Cladosporium cladosporioides, Bipolaris sorokiniana and Fusarium graminearum and 11 did not effect germination of Triticum aestivum. Aqueous extracts of nim, coriander, mutamba and mango reduced the germination of Triticum aestivum seeds.